A MULTIMODAL ANALYSIS OF UMRAH PILGRIMAGE ADVERTISEMENT - Mohammad Muhassin (Jurnal Education and Development, 2022)
Numerous studies have conducted multimodal analysis on the advertising media of goods and services, but the multimodality on an Islamic-themed advertisement has not been explored. This study aims to explore visual and verbal modes employed in Umrah pilgrimage advertisement, the meanings conveyed by the modes, and the meaning relations built by the modes to strengthen the advertisement message. This is a qualitative study using a multimodal analysis framework. Visual and verbal data were obtained from Umrah pilgrimage advertisement of Silver Liners travel agency accessed from www.silverliners.pk. Utilizing the generic structure framework of advertising (Cheong, 2004), visual data were analyzed by Visual Grammar (Kress & van Leeuwen, 2006) and verbal data were scrutinized by Systemic Functional Grammar (Halliday, 2004; Halliday & Matthiessen, 2014). Meanwhile, the intermodal meaning relations were viewed from Intersemiotic Complementarity (Royce, 2007). The study found that the advertisement had all the generic structures, namely lead, display, visual emblem, announcements, enhancer, verbal emblem, tag, and call-and-visit information. In verbal modes, the nominal groups represent the ideational meaning, whereas the imperative clause serves as ideational, interpersonal, dan textual meanings. In addition, visual modes include representational, interactive, and compositional meanings. Verbal and visual modes support each other to form cohesion through the relations of repetition, synonymy, homonymy, meronymy, and collocation. With the cohesion, the message of the advertisement conveyed to the readers becomes more communicative and persuasive so that it can arouse the readers’ interest in using the product services of the company.